2022
DOI: 10.46743/2160-3715/2022.5265
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ and Teachers’ Wellbeing During COVID-19 in Bangladesh: A Qualitative Enquiry

Abstract: The wellbeing of teachers and students has emerged as a common concern in research studies in recent times, specifically during the critical period of COVID-19. Based on the findings drawn from the qualitative data through focus group discussions of five groups of teachers (16 females and 8 males) and students (10 males and nine females) at the tertiary level of education in Bangladesh, this paper shows that online teaching during COVID-19 is affected by personal and social challenges, and consequently, both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Further findings of a qualitative nature available in several of our reviewed studies explicitly elaborate on a set of work-related sources that negatively impacted TWB during the COVID-19 pandemic. Data derived from focus group discussions with university staff conducted by [132] in Bangladesh revealed yet again that (i) the availability of and access to infrastructural and material resources (e.g., limited access to Internet facilities and technological support, fear of monitoring and flaws while teaching in synchronous learning sessions, income worries) and (ii) the increased bulk of administrative and teaching workload amidst the insurmountable COVID-19 circumstances seriously impaired faculty members' physical and mental health, leading to acute physical discomforts (e.g., musculoskeletal, vision problems, and headache) caused by prolonged engagement with online teaching activities and high psychological pressure experienced when faced with the prospect of reduced salaries and losing their job following low student enrollment rates. In Chan et al's [133] study conducted in the first few months of COVID-19, intensified levels of task stress (59%) related to tremendous workload and perceived job ambiguity (over 51%) led to emotional exhaustion and feelings of perplexity for the majority of elementary school teachers, with debilitating effects for their general well-being and teaching efficacy.…”
Section: A Twb Stressors During the Covid-19 Eramentioning
confidence: 99%
“…Further findings of a qualitative nature available in several of our reviewed studies explicitly elaborate on a set of work-related sources that negatively impacted TWB during the COVID-19 pandemic. Data derived from focus group discussions with university staff conducted by [132] in Bangladesh revealed yet again that (i) the availability of and access to infrastructural and material resources (e.g., limited access to Internet facilities and technological support, fear of monitoring and flaws while teaching in synchronous learning sessions, income worries) and (ii) the increased bulk of administrative and teaching workload amidst the insurmountable COVID-19 circumstances seriously impaired faculty members' physical and mental health, leading to acute physical discomforts (e.g., musculoskeletal, vision problems, and headache) caused by prolonged engagement with online teaching activities and high psychological pressure experienced when faced with the prospect of reduced salaries and losing their job following low student enrollment rates. In Chan et al's [133] study conducted in the first few months of COVID-19, intensified levels of task stress (59%) related to tremendous workload and perceived job ambiguity (over 51%) led to emotional exhaustion and feelings of perplexity for the majority of elementary school teachers, with debilitating effects for their general well-being and teaching efficacy.…”
Section: A Twb Stressors During the Covid-19 Eramentioning
confidence: 99%
“…Online assessments appear to be good for saving time, human labor, and test-related costs. However, in online education and assessment in the context of Bangladesh, recent studies (Bashir et al, 2021;Roshid et al, 2022;Sultana et al, 2022) have identified more challenges than benefits, some of which are discussed in the following sections.…”
Section: Beneficial Effects Of Online Assessment (Especially Of Quizz...mentioning
confidence: 99%
“…There are some research studies conducted in Bangladesh that reported prevalence of mental healthrelated challenges among higher educational institute (HEI) students taking online lessons and tests (Rahman et al, 2021) The challenges include moderate to extremely severe depression, anxiety, and stress (Islam, Barna, et al, 2020;Islam, Sujan, et al, 2020). Sultana et al (2022) report students' concerns over clarity and fairness in online assessment. Moreover, Dutta and Smita (2020) identified the following seven challenges of remotely conducted educational programmes: university closure, disruptions in learning, loss of social interaction, physical health problems, mental health problems, shifting to online education, and financial crisis and parental involvement.…”
Section: Online Assessment In Bangladeshi Higher Educationmentioning
confidence: 99%
“…Within a short period, a considerable amount of literature on COVID-19 has been produced that focuses on HEIs’ responses to the pandemic-induced challenges, new developments and transformations in HE that include c ampus closure, social distancing, masking and transition to emergency online remote learning and assessment (Freeman et al, 2021; Khan et al, 2021 ; Pham and Ho, 2020; Kabir et al, 2022). This fast-rising literature also delves into issues of equity, access, the digital divide, and students’ mental and emotional wellbeing as exposed and escalated by the pandemic (Islam et al, 2020; Sultana, et al, 2022; Roshid et al, 2022). Likewise, the pandemic has led to new forms of mobilities in higher education and opened up alternative mobility options for students in Asia (see Gu et al, 2023 this Special Issue for example).…”
Section: Introductionmentioning
confidence: 99%
“…Universities have not implemented adequate redistributive policies in many contexts in the COVID-induced newly emerged situation and have not removed institutional mechanisms discriminating against low-income, vulnerable and marginalised communities. Instead, in many universities globally, the pandemic manifested itself as neoliberal governance, market reform and catastrophe capitalism, all of which pay scant attention to human wellbeing (Watermeyer et al, 2021; Sultana et al, 2022). Conversely, it is believed that institutional integrity and accountability and acknowledging the value of HE in furthering social equity will be crucial aspects of a successful COVID-19 crisis response (Blankenberger and Williams, 2020).…”
Section: Introductionmentioning
confidence: 99%